Single phase bridgeless welding source with reduced semiconductor devices and improved power quality - Kumar, Manoj; Singh, Sanjeev (International Journal of Engineering and Technology, 2019)
This paper presents a single phase bridgeless (BL) converter-based welding source with reduced semiconductor devices with improvement power quality at AC mains. The proposed BL welding source consists of two stages configuration. In first stage configuration bridgeless boost converter operated in continuous conduction mode (CCM), to achieve power factor near unity and input source current less than 5%. In second stage isolated two switch forward converter (TSWFC) is used to drive welding load with high frequency step down transformer (HFT). HFT provide electrical isolation between input supply and welding load. Output current control with short circuit handling capability is also ensured to achieve smooth and strong welding. The removal of diode bridge rectifier in BL converter at the input side, results in conduction loss reduction, increased efficiency and better thermal stability as compared to other conventional power factor correction (PFC) rectifiers. The controller performance is simulated in MATLAB SIMULINK and realized on a hardware prototype for validation of proposed concepts. The obtained results are presented for demonstration of effectiveness of proposed concept. Â Â Â